PENGARUH PRUDENCE, PERSISTENSI LABA, STRUKTUR MODAL DAN KEBIJAKAN DEVIDEN TERHADAP KUALITAS LABA - Nurdianti, Aulia; Anggraini, Anggun (Jurnal Nusa Akuntansi, 2024)
This research aims to provide empirical evidence regarding the influence of Prudence, Earnings Persistence, Capital Structure and Dividend Policy on Earnings Quality. The Quality of Earnings variable is measured by the Quality of Earnings Ratio, Prudence is measured by the KNSV Index, Earnings Persistence is measured by the Profit Persistence Index, Capital Structure is measured by DAR & Dividend Policy is measured by DPR. This type of research is quantitative research with a population of LQ45 companies registered on the IDX for 2018-2022. The sample in this study used a purposive sampling method, obtaining 17 companies. The data analysis technique uses multiple linear regression analysis methods using the Eviews 10 software program. The research results show that Prudence, Profit Persistence, Capital Structure and Dividend Policy simultaneously have a significant effect on Earnings Quality. Prudence partially has no effect on Earnings Quality. Partial Profit Persistence has no effect on Earnings Quality. Capital Structure partially has a significant positive effect on Earnings Quality. Dividend Policy partially has no effect on Earnings Quality.